(untitled) (Revista Internacional de Formação de Professores, 2018)
This paper aims to present the results of a mapping learning assessment of two high schools located in São Paulo state, region of Assis city. These schools were selected according to their results in Assessment System of School Achievement in São Paulo State, called SARESP, from the year of 2013. The objective was to describe, analyse and interpret teaching and evaluation practices carried out in public high schools in Assis region and verify if there are significant differences between the two schools surveyed that could justify the differences found in the results of SARESP. The methodology was qualitative based in class observations, questionnaires and interviews among students and teachers. As results, we verified significant differences between the two schools related to the teaching and evaluation practices adopted by the teachers. Hence, it was possible to stablish import relations among these practices that reflect in the results reached in SARESP. We also emphasized the importance of discussions involving teachers and students about the pedagogical practices developed by the teachers, mainly evaluation practices, in order to relate them to the school success or failure of their students.